Kadar hemoglobin, status gizi, pola konsumsi makanan dan Kualitas hidup pasien Thalassemia - Isworo, Atyanti; Setiowati, Dwi; Taufik, Agis (Jurusan Keperawatan FIKES UNSOED, 2012)
Thalassemias are a group of genetic (inherited) blood disorder characterized by a deficiency of hemoglobin that causing chronic anemia which may result in a decrease in appetite and short on some vitamins and minerals. Besides chronic anemia that occurs needs to get blood transfusions. providing continuous blood transfusion can not be separated from the problem. In addition to the problem of iron accumulation in the body, giving a continuous bloodÃ‚Â transfusions make children feel hopeless and unclear about his future. These conditions has implications for quality of life. The purpose of this study was to identify hemoglobin level, nutrition status, food frequency and quality of life. This study used an descriptive study, recruited 32 respondents by purposive sampling method at Banyumas Residence. The result revealed that mean hemogobin level 7,99 gr/dL; poor nutrition status 59,94%, food frequency were rice 2,87 x/day, chicken egg 0,89 x/day, carrot and banana 1,02 x/day and 0,61 x/day. Quality of life measurement found that mean QoL was 67,24Ã‚Â±(9,68).Ke